PENGEMBANGAN MEDIA PEMBELARAN PERMAINAN KARTU NOMOR BERGAMBAR UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATEMATIKA KELAS IV SEKOLAH DASAR - Oktavia Duwi Salsadila Rahmadhani; Bramianto Setiawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this research is to assess the level of mathematical understanding among fourth-grade students regarding the material on fractions. Issues arise due to the lack of interactive learning media and the lack of enthusiasm from students during the learning process, resulting in low student motivation and subpar learning outcomes. Therefore, the aim of this research is to develop learning media, which is created in the form of a card game featuring numbers that makes mathematical concepts more concrete and interactive. This research uses the Research and Development (R&D) method utilizing the ADDIE model through the following five stages: analysis, design, development, implementation, and evaluation. The subjects of the study are 30 students from class IV D at SDN Sukaresmi 06, selected using saturated sampling techniques. Data was collected through expert validation, pretests, posttests, and feedback from teachers and students. The research findings indicate that the media is highly effective, practical.